2018
DOI: 10.1002/eat.22961
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptomatology and body mass index are associated with readers' expectations about character behavior: Evidence from eye‐tracking during reading

Abstract: Objective Many theories have been put forward suggesting key factors underlying the development and maintenance of eating disorders, such as: unhealthy food‐related cognitive biases, negative body attitude, and perfectionism; however, underlying cognitive processes associated with eating disorder symptomatology remain unclear. We used eye‐tracking during reading as a novel implicit measure of how these factors may relate to eating disorder symptomatology. Method In two experiments, we monitored women's eye mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
5
8
0
Order By: Relevance
“…Instead, we used the EDE-Q, which is a validated and reliable questionnaire that can provide a reasonable approximation of eating disorder symptoms, shown to be comparable to the clinical evaluation tool (the EDE) (Berg et al, 2012). It is also important to note that, as has been found in other studies (Ralph-Nearman & Filik, 2018), the EDE-Q scores also differed slightly from those from another community sample of young females from Australia (Mond et al, 2006). This is perhaps not unusual, as eating disorder symptomatology may vary across cultures (Mond et al, 2006;Tozzi et al, 2005).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Instead, we used the EDE-Q, which is a validated and reliable questionnaire that can provide a reasonable approximation of eating disorder symptoms, shown to be comparable to the clinical evaluation tool (the EDE) (Berg et al, 2012). It is also important to note that, as has been found in other studies (Ralph-Nearman & Filik, 2018), the EDE-Q scores also differed slightly from those from another community sample of young females from Australia (Mond et al, 2006). This is perhaps not unusual, as eating disorder symptomatology may vary across cultures (Mond et al, 2006;Tozzi et al, 2005).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, specific cognitive biases have been detected with this tool related to both BMI and eating disorder symptoms (see e.g., Ralph-Nearman et al, 2019, for a review). One recent study aimed to investigate information processing strategies under more natural conditions, specifically, by tracking eye movement behaviour during a natural reading task (Ralph-Nearman & Filik, 2018a). In this prior study, female participants had their eye movements monitored while they read body-, food-, or perfectionism-related texts in third-person perspective (Experiment 1) or second-person perspective (Experiment 2).…”
Section: Using Eye-tracking To Investigate Information Processing Str...mentioning
confidence: 99%
“…While these explicit measures have provided a useful means of assessing the broad emotional consequences of verbal irony, they can be limited by response biases and errors, necessarily involve disruption to processing, and do not assess processing in real-time. More recently, a few studies have applied online measures, such as eventrelated brain potentials (ERPs) and eye-tracking, to investigate how readers keep track of temporal and emotional shifts in stories, and have demonstrated that readers are sensitive to mismatches between a character's expected and described emotional states (Komeda, & Kusumi, 2006;Leuthold, Filik, Murphy, & Mackenzie, 2012;Ralph-Nearman & Filik, 2018;Rinck, & Bower, 2000;Vega, 1996;Zwaan, 1996).…”
Section: Emotional Processing Of Ironic Vs Literal Criticism In Autimentioning
confidence: 99%